Late Aptian angiosperm pollen grains from Patagonia: earliest steps in flowering plant evolution at middle latitudes in southern South America - Llorens, Magdalena (2015)
The angiosperm pollen record from the Anfiteatro de Ticó and Punta del Barco formations (Baqueró Group) is reported. The relevance of these floras is that they are accurately dated as late Aptian, and one of the oldest floras southern South America with fossil angiosperms. Twelve samples were studied, showing Clavatipollenites and Retimonocolpites as dominant types. A new species, Jushingipollis ticoensis sp. nov., is proposed. A doubtful angiosperm pollen grain, Lethomasites sp., is also identified and described. A multivariate analysis of similarities between different Early Cretaceous angiosperm pollen assemblages suggests that the Baqueró Group assemblages have great similarities with other coeval units from Argentina, Australia and United States, which were located in a similar paleolatitude.